2012
DOI: 10.1177/0333102412468671
|View full text |Cite
|
Sign up to set email alerts
|

Migraine is a risk factor for sudden sensorineural hearing loss: A nationwide population-based study

Abstract: This population-based study demonstrates that migraine is associated with an increased risk of idiopathic SSNHL, which, however, is a rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 29 publications
6
55
0
1
Order By: Relevance
“…In a large populationbased study in Taiwan, an association between migraine and hearing loss has recently been reported. 32 In addition, there have been previous reports of sudden hearing loss and migraine in Meniere's disease. [33][34][35][36] However, the hearing loss developed in migraine patients at an older age, and their family members did not have hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In a large populationbased study in Taiwan, an association between migraine and hearing loss has recently been reported. 32 In addition, there have been previous reports of sudden hearing loss and migraine in Meniere's disease. [33][34][35][36] However, the hearing loss developed in migraine patients at an older age, and their family members did not have hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In the migraine cohort study of Chu et al, [31] including migraine patients looking for active medical assistance and patient population gathered from National Health Insurance Research Database, migraine was founded related to increase of SNHL risk when two cohort were composed by minimalizing the difference as much as possible in terms of vascular risk factors such as accompanier major cardiovascular diseases and serebrovascular diseases. In Chu et al, [31] study, SNHL developed during the follow-up in 134 (0.3%) of 51.400 subjects, it also developed in 43 (0.4%) subjects of migraine cohort and 91 subjects of matched control cohort (Fisher exact test, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as DFNA5 could also play a role in the etiology of hearing loss while involving cancer [9]. Migraine as a risk contributor for hearing loss was recently observed in population-based studies and the clinical setting, although the quality of study designs including the consideration of covariates would need to be revisited [10][11][12]. The relationship of migraine and hearing loss was first described in a case report back in 1987 [13].…”
Section: Main Findingsmentioning
confidence: 99%